Islamic Ethics and Modern Governance: The Case of Mental Revolution in Papua’s Religious Affairs Office - Luhuringbudi, Teguh; Yahya Komarudin; Mowafg Abrahm Masuwd; Massuhartono; Alhusni; M. Zaki (Al-Wasatiyah: Journal of Religious Moderation, 2025)
The present study demonstrated that the "Contextual Transformative Ethics" model facilitates the integration of Islamic ethical values into contemporary governance practices, thereby enhancing national commitment and tolerance in Papua through the "Rembuk Amanah" mechanism, which respects local traditions.This research paper examined the synergy between Islamic ethics and modern governance in the implementation of a mental revolution in the Papua Religious Affairs Office through an analysis of value-based institutional transformation. This study addresses a significant gap in the extant literature on ethics in bureaucratic practice. While there are numerous studies on the subject, there is a paucity of specific models that integrate Islamic ethical values with modern governance approaches in diverse socio-cultural contexts, such as Papua. The objective of this study is to identify a model of adaptation of Islamic ethical values into modern bureaucratic practices, with a focus on the social and cultural conditions of Papuan society. The data collection process entailed participatory observation in five KUA, in-depth interviews with 24 respondents, including officials, staff, and service users, as well as the analysis of policy documents and operational records of institutions during the period 2020-2024. The analysis employed Tariq Ramadan's contemporary Islamic ethics theoretical framework, Ostrom-Basurto's adaptive governance model, and George-Sim's authentic leadership approach through the stages of reconciliation, presentation, and data construction. The research findings revealed the unique phenomenon of "Rembuk Amanah" as a cultural negotiation mechanism between Islamic values and local wisdom. Furthermore, the identification of the "Agent of Change" group, which has developed a digital-based service system while maintaining a traditional personal touch, was noted. The research yielded a model of "Contextual Transformative Ethics" and the concept of "Responsive-Adaptive Governance," which describes the dynamic interaction between bureaucratic structures, ethical values, and cultural contexts in institutional transformation. The study's limitations stem from its narrow geographical scope and cross-sectional design, which precludes a comprehensive analysis of long-term change.